Increased NOX-dependent ROS production and proportionally enhanced antioxidant response in white adipose tissue of male rats - Jessica de Freitas Nascimento; Keciany Alves de Oliveira; Paula Alexandre de Freitas; Júlia de Araújo Marques Falci; Renata Prado Vasconcelos; Saulo Chaves Magalhães; Talita Mendes Farias; Maria Isabel Cardoso Alonso-Vale; Adriano Cesar Carneiro Loureiro; Denise Pires de Carvalho; Rodrigo Soares Fortunato; Ariclécio Cunha de Oliveira (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: This study aimed to investigate the redox balance in subcutaneous and retroperitoneal fat pads of male and female Wistar rats. Materials and methods: The study analyzed the activity and gene expression of the antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase, along with the production of NADPH oxidases dependent on H2O2 and gene expression of NOX1, NOX2, and NOX4. Results: The retroperitoneal fat pad in males compared with females had greater NOX2 and NOX4 expression, along with higher superoxide dismutase activity. Additionally, their subcutaneous fat pad had greater NOX4 expression and higher intracellular H2O2 production, together with greater expression and activity of both superoxide dismutase and catalase. Conclusion: The white adipose tissue of male rats had greater reactive oxygen species (ROS) production compared with that of female rats, but also a proportionally greater antioxidant response. These findings are important for ongoing investigations into how sex differences may be linked to the development of metabolic diseases and the unique susceptibilities of each sex.